2023
DOI: 10.1200/jco.2023.41.4_suppl.206
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional observational study evaluating the incidence and the clinicopathological characteristics of NeoRAS wild-type metastatic colorectal cancer.

Abstract: 206 Background: The ’’Neo RAS’’ phenomenon, in which tissue rat sarcoma viral oncogene homolog ( RAS) status converts from mutant (MT) to wild-type (WT) after treatment in metastatic colorectal cancer (mCRC), is gaining attention because epidermal growth factor receptor (EGFR) inhibitors, which were originally considered to be ineffective, may converted to be effective. This multi-center study investigated its incidence and clinicopathological characteristics that are still unclear. Methods: 107 mCRC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Sato et al reported that all patients ( N = 4) with tissue RAS Q61H mutations had Neo RAS WT 30 . Yoshinami et al also showed a high incidence of Neo RAS among patients with tissue RAS MTs in exons other than the KRAS exon 2 (5/8, 62.5%), and this finding was related to the emergence of Neo RAS WT in their multivariate analysis 33 , 34 . Loree et al 35 similarly described that the allelic fractions of MTs in KRAS exons 3 and 4 and NRAS were lower than those of KRAS exon 2 MTs.…”
Section: Discussionmentioning
confidence: 92%
“…Sato et al reported that all patients ( N = 4) with tissue RAS Q61H mutations had Neo RAS WT 30 . Yoshinami et al also showed a high incidence of Neo RAS among patients with tissue RAS MTs in exons other than the KRAS exon 2 (5/8, 62.5%), and this finding was related to the emergence of Neo RAS WT in their multivariate analysis 33 , 34 . Loree et al 35 similarly described that the allelic fractions of MTs in KRAS exons 3 and 4 and NRAS were lower than those of KRAS exon 2 MTs.…”
Section: Discussionmentioning
confidence: 92%